HUBUNGAN LINGKUNGAN TERHADAP PERSEPSI REMAJA TENTANG PERNIKAHAN DI BAWAH UMUR DI SEKOLAH MENENGAH PERTAMA KABUPATEN BOGOR TAHUN 2022 - Zahra Gita Disayang (2022)
Underage marriages have continued to increase since the Covid-19 pandemic in Indonesia, including Bogor Regency. The impact of underage marriage is a long-term problem including health and economic problems. The purpose of the study was to determine the relationship between the environment and adolescents' perceptions of underage marriage. The study design used a cross-sectional and data collection was completed by a questionnaire. The study was conducted on eighth-grade students at SMP Negeri 1 Tamansari, SMP Negeri 1 Leuwisadeng, and SMP Negeri 2 Megamendung with a total population of 1,049 students. The total sample is 282 respondents with the technique of purposive sampling. The research instrument used various modified questionnaires. The data analysis used chi-square and multiple logistic regression. The results showed that gender (p-value = 0.008), family (p-value = 0.000), and culture (p-value = 0.000) have a relationship with adolescents' perceptions of underage marriage, while age, pandemic situations, parents' education, parents' income, ethnicity, peers and social media there is no relationship with adolescents' perceptions of underage marriage. Family is the most related variable in this study. Families can provide attention and supervision to adolescents and provide adolescents with opportunities to carry out positive activities.